Use of Multimedia in the Design of Educational Websites and their Role in Enhancing the Cognitive Aspect of the Learner (Al-Academy, 2019)
Multimedia is one of the most important elements of modern educational media and must be used in educational websites in order to disseminate knowledge on a large scale and should be used to provide scientific information to all, as the current research tried to explore the possibilities of employing them in the design of educational websites and highlight their role in promoting the scientific aspects of the user. This study included four axes, the first of which was devoted to the introduction which includes the problem of research, its importance, objectives and its objective, temporal and spatial limitations, which were limited to the study of the main pages of Arabic educational websites published in 2019. The second axis contained the theoretical framework which included two sections that introduce the concepts of multimedia employment in designing websites and using them in the field of education. The third axis is to clarify the research procedures and methodology, which was according to the descriptive analytical method. Two samples were selected. The selection was intentional. The analysis was conducted according to a form designed to achieve the goal of the research and draw the required results. The fourth axis was devoted to presenting the research results and the most important conclusions, recommendations and theoretical and practical proposals